Sleep disorders in polycystic ovary syndrome: influence of obesity and hyperandrogenism - Hachul,Helena (2019)
SUMMARY OBJECTIVE: This study aims to evaluate the sleep of subjects with polycystic ovary syndrome (PCOS), with and without hyperandrogenism, in comparison with a healthy control group and examine the effects of hyperandrogenism and obesity on sleep parameters. METHODS: A total of 44 volunteers were recruited to participate in the study. Clinical, biochemical and polysomnographic parameters were used to diagnose PCOS and hyperandrogenism. The evaluation of sleep quality was made using validated questionnaires and polysomnography test. The frequency of obstructive sleep apnea was also compared between the groups. RESULTS: The study revealed that women with PCOS presented poorer subjective sleep quality, increased incidence of snoring and a higher risk of obstructive sleep apnea, based on the Berlin questionnaire. Also, after adjusting for body mass index, PCOS subjects had rapid eye movement (REM) time lower than those in the control group. PCOS women versus those without hyperandrogenism did not differ on any sleep measurement. Women with obstructive sleep apnea were only diagnosed in the PCOS group. CONCLUSIONS: Our results indicate that PCOS impairs subjective sleep quality, as well as objective sleep quality, due to a reduction in REM sleep stage time in women diagnosed with the syndrome. Obesity affected sleep-related parameters but hyperandrogenism had no effect. Only the PCOS group had obstructive sleep apnea diagnosis.